The Use of Skill Academy by Ruang Guru In Improving Elesp Students’ Toefl Scores In Listening Section - Y, Yolanda; Ibrahim, Moh. Syahrun; Badu, Helena; Otoluwa, Moon H.; Husain, Nurlaila (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examined the effectiveness of the Skill Academy by Ruang Guru in enhancing students' listening comprehension skills for the TOEFL listening section. Using a quantitative pre-test and post-test design, 15 participants from the English Language Education Study Program underwent four sessions of TOEFL listening preparation through the Skill Academy platform. The study aimed to evaluate the platform’s impact on standardized test preparation and contribute to research on online education. A paired t-test analysis revealed a calculated value of 5.4, surpassing the table value of 2.145 at d_f = 14 and α = 0.05 (two-tailed), leading to the rejection of the null hypothesis. This indicated a significant improvement in participants' scores after the intervention. The findings suggest that Skill Academy effectively enhanced students' listening skills for the TOEFL, proving its value as an exam preparation tool. This research underscores the potential of online learning platforms in improving targeted test skills. Future studies could examine the long-term effects of such programs and compare different platforms to optimize TOEFL preparation strategies